Profile of open-start problem-solving with context Sarangan Lake viewed students' learning styles in junior high school - Murtafiah, Wasilatul; Wardani, Yulia Nindi; Darmadi, Darmadi; Widodo, Sri Adi (Intelektual Pustaka Media Utama, 2024)
This study aims to reveal the profile of open-start problem-solving with ethnomathematics regarding student learning styles. This research is a qualitative research study on 3 out of 31 students of Junior High School of 3 Magetan taken by purposive sampling. The three students carried out four stages: understanding the problem, planning problem-solving strategies, implementing problem-solving strategies, and reviewing again. The results of the research show that students with a visual learning style solve problems by understanding problems through writing known and being asked and drawing illustrations, planning problem-solving strategies by making examples, carrying out solving strategies by working on the calculation process; students with an auditory learning style solve problems by understanding problems through writing known and being asked, planning strategies by making problems and formulating formulas used, implementing solutions by doing calculations and reviewing; students with a kinesthetic learning style solve problems by understanding issues through writing known and being asked, making examples and writing the formulas used, carrying out solving strategies by applying the calculation process and reviewing the results obtained. However, of the three styles, the results of the accepted work were not correct because they did not write down the conclusions and were not thorough enough.